A Review of the Complete Systematic Land Registration (PTSL) Program and Its Accompanying Taxes - Retno Kadarukmi, Maria Emelia (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2025)
In theory, the goal of land registration is to provide legal certainty to Indonesians. The government, through the Ministry of ATR, is actively conducting the first round of land registration under the Complete Systematic Land Registration Program (PTSL). Land registration can be carried out systematically or sporadically. However, after the issuance of land rights certificates, the community faced issues and uncertainty during the PTSL implementation. This was due to the lack of socialization regarding the PTSL program and unclear regulations concerning the due dates for BPHTB and income tax obligations. To achieve legal certainty regarding land rights, this research aims to examine the implementation of the PTSL program in relation to the collection of BPHTB and income tax. The research employs a normative juridical methodology. The findings, which include opinions and recommendations, suggest that while the execution of the PTSL program provides some legal clarity about the community's land rights status, it also causes confusion among the community regarding the responsibilities for income tax and BPHTB. This is because the community has already been exposed to propaganda from the Government that the first land registration through the PTSL program is free. Suggestions to the Government to immediately make regulations to regulate BPHTB and Income Tax and provide tax relief by imposing a zero percent rate.